Defective microglial development in the hippocampus of Cx3cr1 deficient mice - Pagani, Francesca; Paolicelli, Rosa C.; Murana, Emanuele; Cortese, Barbara; Di Angelantonio, Silvia; Zurolo, Emanuele; Guiducci, Eva; Ferreira, Tiago A.; Garofalo, Stefano; Catalano, Myriam; D’Alessandro, Giuseppina; Porzia, Alessandra; et al. (Frontiers in Cellular Neuroscience, 2015)
Microglial cells participate in brain development and influence neuronal loss and synaptic maturation. Fractalkine is an important neuronal chemokine whose expression increases during development and that can influence microglia function via the fractalkine receptor, CX3CR1. Mice lacking Cx3cr1 show a variety of neuronal defects thought to be the result of deficient microglia function. Activation of CX3CR1 is important for the proper migration of microglia to sites of injury and into the brain during development. However, little is known about how fractalkine modulates microglial properties during development. Here we examined microglial morphology, response to ATP, and K+ current properties in acute brain slices from Cx3cr1 knockout mice across postnatal hippocampal development. We found that fractalkine signaling is necessary for the development of several morphological and physiological features of microglia. Specifically, we found that the occurrence of an outward rectifying K+ current, typical of activated microglia, that peaked during the second and third postnatal week, was reduced in Cx3cr1 knockout mice. Fractalkine signaling also influenced microglial morphology and ability to extend processes in response to ATP following its focal application to the slice. Our results reveal the developmental profile of several morphological and physiological properties of microglia and demonstrate that these processes are modulated by fractalkine signaling.